A distinct APC pathogenic germline variant identified in a southern Thai family with familial adenomatous polyposis - Worrawit Wanitsuwan; Sukanya Vijasika; Pichai Jirarattanasopa; Sukanya Horpaopan (BMC, 2021)
Abstract Background Familial adenomatous polyposis (FAP) is caused by pathogenic germline variants in the APC gene. To date, multiple pathogenic variants in coding regions, splice sites, and deep intronic regions have been revealed. However, there are still pathogenic variants that remain unidentified. Methods Twenty-nine primer pairs flanking exons 2-16 (i.e., coding exons 1-15) of APC and their exon-intron junctions were used for germline pathogenic variant screening in Southern Thai patients with familial adenomatous polyposis (FAP). Transcription analysis was performed to confirm the pathogenicity of a splice site deletion of intron 10. Family members were interviewed for clinical histories. Blood samples were collected from 18 family members for a segregation study. Subsequently, clinical data of affected members were collected from the hospital databases. Results We found a distinct heterozygous 16-bp deletion at the splice donor site of intron 10 leading to a skipping of exon 10 which was confirmed by transcript analysis (APC: c 1312 + 4_1312 + 19del, r.934_1312del). Predictive testing for the pathogenic APC variant in 18 of the proband's family members (ten healthy and eight affected) from three generations showed the same heterozygous germline pathogenic variant in eight affected adult members (15-62 years old) and two children (7 and 10 years old). Seven of the ten carriers of the disease-causing variant had undergone colonoscopy, and colonic polyps were found in all cases, which confirmed the segregation of the inherited pathogenic variant. The phenotypic spectrum was found to vary within the family; and some affected family members exhibited extracolonic manifestations. Conclusions To our knowledge, the pathogenic APC variant, c.1312 + 4_1312 + 19del, r.934_1312del, has not previously been reported. This study is one of the few reports describing the phenotypic consequences of a pathogenic APC variant in a high number of affected family members.